Sistem Pendukung Keputusan untuk Memilih Program Kesehatan Sekolah Menggunakan COPRAS - M. Ari Prayogo; Muhammad Labib Jundillah; Febri Ramanda; Muhammad Shodiq; Riendy Riendy (Sistem Pendukung Keputusan dengan Aplikasi, 2025)
The School Health Program is a strategic initiative aimed at improving students’ health within the educational environment. However, selecting the most appropriate program often requires consideration of multiple complex criteria. This study develops a Decision Support System (DSS) using the COmplex PRoportional ASsessment (COPRAS) method to assist schools in determining the best health program. The alternative programs analyzed include Reproductive Health, Healthy School Cleanliness Competition, Smoke-Free School Area, Prevention of Drug Abuse (NAPZA), and Disease Control. The evaluation was conducted based on six main criteria: Implementation Cost, Student Participation, Program Effectiveness, Long-Term Health Impact, Relevance to School Needs, and Ease of Implementation. The results indicate that the third alternative (A3), namely the Smoke-Free School Area, is the most suitable school health program, achieving a utility value (Ui) of 100% among the five alternatives considered. This system is expected to make the decision-making process more objective, efficient, and supportive of fostering a healthier, more productive, and sustainable school environment.